Cultural Influences on the Assessment of Children’s Pain - G Allen Finley; Ólöf Kristjánsdóttir; Paula A Forgeron (Pain Research and Management)
Culture is commonly regarded as a factor in pain behaviour and experience, but the meaning of the term is often unclear. There is little evidence that pain perception is modified by cultural or ethnic factors, but pain expression by children and interpretation by caregivers may be affected by the culture of the patient or the caregiver. The present paper examines some of the research regarding cultural influences on children’s pain assessment, and addresses directions for future research. A focus on cultural influences should not distract clinicians from the need to be sensitive to individual beliefs and attitudes.